Karakteristik dan Peranan Lembaga Petani Pemakai Air Dalam Mendukung Produktivitas Hasil Padi di Kecamatan Toboali Kabupaten Bangka Selatan - Prabowo, Ari (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Based on data of Bangka Belitung Island in 2014, the growth race of production has increased during 2010-2013. However, rice productivity decrease because at the same time harvested land area increased. This study purpose to inspect the characteristic and the role of organization of water user farmer in support to productivity of rice yield in Toboali, South Bangka. This study uses descriptive quantitative method with identify the potential and problems owned by irrigation area in study area and SWOT analysis. The result showed quality of irrigationâ€™s construction and the availability of irrigation water resources have decreased. Then, human resource capacity and the relationship between the institutional with related stakeholder still low. While from the result of SWOT analysis selected W-T strategy that is minimize and strengthenÂ the weakness by overcoming and avoiding the threat.